Pengaruh Penangkaran terhadap Profil Eritrosit Lumba-lumba Hidung Botol dari Perairan Laut Jawa - Guntari Titik Mulyani; Yuda Heru Fibrianto; Teguh Budipitojo (Jurnal Sain Veteriner, 2012)
In the Java Sea, there are a lot of dolphins, that often snagged fishing nets. While In Indonesia, bottlenosedolphins are mammals protected water. The aims of this research was to study the erythrocytes profile inbottlenose dolphins before and after the captivity. Seven dolphins were used in this research. Blood samples weretaken out from the superficial vein of tail for examination of the number of erythrocytes, hemoglobin levels andvalue of hematokrit. Sampling was done when the dolphins appointed from the waters of the Java Sea and afterexperiencing dolphin captivity in PT. WSI, Kendal, Central Java. The data before and after captivity were compared and tested with the statistical analysis on the level of significance of the paired t-test 95%. The results showed the significant increase in the number of erythrocytes, hemoglobin levels and the values of hematokrit significantly. It was concluded that captivity done by WSI Corporation, Kendal, Central Java did increase the profile of erythrocytes in bottlenose dolphins.Keyword : Bottlenose dolphins, captivity, profile erythrocytes, superficial vein of tail, paired t-test